Information Modeling in Creative Process – Innovative possibility of BIM in architectural and urban design processes - Motta, Silvio Romero Fonseca (DISEGNARECON, 2013)
The paper studies the use of Building Information Modeling - BIM in the design process and their contributions to do best buildings. For this, are defined the stages of the design process and proposed a theoretical model of the design process, by analogy to the theory of knowledge. In the theoretical model were considered the approaches of knowledge empiricist and rationalist. It was discussed the consequences of these approaches in the stage of the design of the idea. It was also presented a case study of practical use of BIM. The case study was analyzed against the theoretical model proposed. The conclusion indicated the importance of the use of BIM in the phase of conception of the idea, especially through simulations and (critical) tests (of our hypothesis) of design.